2011
DOI: 10.1111/j.1537-2995.2011.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

A rest period before agitation may improve some in vitro apheresis platelet parameters during storage

Abstract: A rest period from 1 to 6 hours may improve some but not all in vitro PLT storage parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…As such, in order to obtain platelet units for research only, apheresis requires special administrative permission and is excessively costly (~$1,000 per unit), Nonetheless, it has been demonstrated that centrifugation has a similar effect in terms of platelet activation and aggregation when compared to apheresis suggesting these two methods of collection are comparable. (38,39) Moreover, in terms of mitochondrial oxygen consumption, our preliminary results showed that by day 5 of storage, platelets donated by apheresis demonstrated were similar to the units processed by centrifugation. Secondly, the volume of the platelet concentrates were approximately 80 mL per unit, which is greatly different from the standard platelet transfusion unit.…”
Section: Discussionmentioning
confidence: 60%
“…As such, in order to obtain platelet units for research only, apheresis requires special administrative permission and is excessively costly (~$1,000 per unit), Nonetheless, it has been demonstrated that centrifugation has a similar effect in terms of platelet activation and aggregation when compared to apheresis suggesting these two methods of collection are comparable. (38,39) Moreover, in terms of mitochondrial oxygen consumption, our preliminary results showed that by day 5 of storage, platelets donated by apheresis demonstrated were similar to the units processed by centrifugation. Secondly, the volume of the platelet concentrates were approximately 80 mL per unit, which is greatly different from the standard platelet transfusion unit.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, with 30 patients in the prasugrel group, this precision was 11%, quite close to the planned precision. Second, we used freshly prepared PRP and the quality of platelets may differ from that of allogenic platelet concentrates [40]. Finally, the ability of non-inhibited platelet supplementation to overcome ADP-Agg max in patients treated with ticagrelor was one of this study's secondary objectives and it cannot be ruled out that the absence of a significant effect from platelet supplementation in this group might be due to a lack of power.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study of aliquots of Amicus PLTs held with and without rest by Skripchenko and colleagues 6 found that rest periods improve PLT morphology (% disc), ESC, and mean levels of CD42b. Whether a rest period enables full resuspension of Amicus units with aggregates could not be determined from the limited number of units utilized in that evaluation.…”
Section: Discussionmentioning
confidence: 94%
“…The extent of improvement of these three variables increased with extending the rest period from 1 hour to 6 hours. Interestingly, these in vitro benefits of an initial rest period before storage were still evident after 5 days of storage 6 . The AABB technical manual and apheresis operating manuals are silent about rest periods; practices at blood centers and hospitals vary.…”
mentioning
confidence: 99%